Investigating whether microsatellites could influence the relative expression level of TLR4 gene in bursa of Rhode Island Red chicken - JAGADEESAN, KRISHNAN; KUMAR, SANJEEV; RAHIM, ABDUL; YADAV, A S; DAS, ANANTA KUMAR (The Indian Journal of Animal Sciences, 2022)
TLR4 gene, vitally linked to resistance to infection with Salmonella enteric serovar Typhimurium in chickens, was chosen as a candidate gene for this investigation to assess the probable impact of microsatellite genotypes on relative expression of TLR4 gene. Our study documented variable expression level of TLR4 gene in tissue bursa of RIR chicken encoded with different microsatellite genotypes. The DD and CC genotypes of MCW0330 microsatellite demonstrated numerically higher mRNA expression than its AA, AC and BD genotypes. Therefore, The MCW0330 genotyping may predict TLR4 gene expression if confirmed by a thorough investigation taking a large number of samples and then would play an important role in host-pathogen genetics with respect to Salmonellosis in poultry.